2022
DOI: 10.3390/foods11233778
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Volatile Organic Compounds in Different Pear Cultivars during Storage Using HS-SPME with GC-MS

Abstract: Aroma, which plays an essential role in food perception and acceptability, depends on various mixture of volatile organic compounds (VOCs). Meanwhile, as a field of metabolomics, VOC analysis is highly important for aroma improvement and discrimination purposes. In this work, VOCs in pear fruits were determined via headspace solid-phase micro-extraction (HS-SPME) combined with gas chromatography–mass spectrometry (GC–MS) to study variations among different cultivars and storage stages. In 12 cultivars of pear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In our current research of pollutants from composting, the increase in temperature and the start of VOC emissions are primarily associated with increased microbial activity [43], as well as subsequent cooling and maturation of the substrate leads to a significant decrease in emissions [44]. In a number of studies, the appearance of VOC has been linked precisely to the creation of anaerobic conditions inside the substrate, resulting in fermentation, rotting and incomplete decomposition of organic matter in the medium [7,17,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our current research of pollutants from composting, the increase in temperature and the start of VOC emissions are primarily associated with increased microbial activity [43], as well as subsequent cooling and maturation of the substrate leads to a significant decrease in emissions [44]. In a number of studies, the appearance of VOC has been linked precisely to the creation of anaerobic conditions inside the substrate, resulting in fermentation, rotting and incomplete decomposition of organic matter in the medium [7,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohols, aldehydes and ketones are the compounds released by microorganisms during the decomposition of plant raw materials. They are formed during fermentation as a result of the reaction of hydrogenation and dehydrogenation, with the change of the carbonyl group to the alcohol group and vice versa [43]. The alcohol content in the emission during composting of FW+WC correlated with the content of esters formed via esterification of alcohols and organic acids (mainly acetic) [43].…”
Section: Discussionmentioning
confidence: 99%
“…It is most frequently used for the qualitative and quantitative determination of VOCs in foods and herbs ( Nekoei and Mohammadhosseini, 2017 ; Nekoei and Mohammadhosseini, 2018 ; Mohammadhosseini et al., 2021 ). HS-SPME-GC-MS approach was proven to be effective in estimating the effects of a season change on volatile compounds in green tea ( Wang et al., 2022c ), analyzing the volatile compounds of traditional Chinese sesame oil ( Chen et al., 2022 ), and monitoring VOCs in pear during storage ( Gao et al., 2022 ). GC-IMS is a suitable approach for separating and measuring VOCs ( Wang et al., 2022d ).…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that volatile organic compounds (VOCs) are emitted as gases from certain solids or liquids products. For example, numerous studies have shown the linkage between variety of products and their VOCs [1][2][3][4]. As a result, VOCs (e.g., formaldehyde, benzene, toluene, trichloroethylene dichloromethane) released into the atmosphere have been directly inducing short-term and long-term adverse effects to human health, leading to atmospheric environmental problems such as haze and photo-chemical smog [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this research is to examine potential correlations between VOCs emitted from insecticides and agricultural applications in the following ways: (1) to estimate the potential insecticide VOC emission based on thermogravimetric analysis (TGA) of insecticide samples; (2) to measure the actual emission of the sample products after their application with portable VOCs gas detector and to compare the actual emission and potential VOC emission of the products; (3) to further analyze their emission characteristics of insecticide VOCs during application and the influence of formulations and meteorological factors. To the best of our knowledge, this represents the first study of field application experiment of pesticide VOCs in China.…”
Section: Introductionmentioning
confidence: 99%